Standardization of a human organ culture model of intestinal inflammation and its application for drug testing - Szikszai, Timea; Lasitschka, Felix; Giese, Thomas; Greulich, Matthias; Lee, Young-Seon; Schiessling, Serin; Leowardi-Bauer, Christine; Saeedi, Mohammed al; Meuer, Stefan; Schröder-Braunstein, Jutta (Journal of immunological methods, 2015)
Targeting early molecular events in intestinal inflammation may represent a useful therapeutic strategy for maintaining remission in inflammatory bowel disease. Recently, we established an intestinal organ culture model (LEL model), which allows to study the initiation of an intestinal inflammatory response in human tissue. In this model, EDTA-mediated depletion of epithelial cells of colonic mucosa results in an instantaneous inflammatory response in resident lamina propria cells, which shows features of intestinal inflammation in vivo. Furthermore, activated immune cells emigrate from the lamina propria onto the luminal side of the basement membrane. Here, we standardize the LEL model and explore its suitability for drug testing. To this end, human mucosal punches of defined surface area were prepared, depleted of epithelial cells, and cultured at an optimized ratio of medium volume/punch area. The intra-assay variability of measurements of inflammatory parameters ranged from 13% for cell migration to 19% for secretion and 30% for tissue gene expression, respectively, of the inflammatory mediators IL-8 and IL-6. Importantly, known suppressive effects of dexamethasone, a drug employed for the treatment of inflammatory bowel diseases, on leucocyte migration, IL8, IL6, and TNF-α production as well as CD86 surface expression by myeloid cells were observed in this model. In conclusion, the present results suggest that the LEL model may represent a useful human experimental system not only for studying initial activation mechanisms in intestinal inflammation but also for evaluating drug compounds for the treatment of mucosal inflammation.
Gesehen am 02.05.2017